Human umbilical perivascular cells (HUCPVCs): a novel source of mesenchymal stromal-like (MSC) cells to support the regeneration of the testicular niche. Issue 1 (January 2017) - Maghen, Leila; Shlush, Ekaterina; Gat, Itai; Filice, Melissa; Barretto, Tanya A; Jarvi, Keith; Lo, Kirk; Gauthier-Fisher, Andrée; Librach, Clifford L
Abstract : The expansion of functional testicular biopsy-derived human spermatogonial stem cells (hSSC) ex vivo may enable the restoration of fertility in pre-pubertal males having undergone gonadotoxic therapies or men with severe male factor infertility. Various somatic cells are known to regulate SSC homeostasis and spermatogenesis in the developing and adult testis. Prior attempts to recapitulate this niche demonstrated the requirement of feeder cells, such as endogenous testicular somatic cells, for germ cell expansion ex vivo . However, this strategy has limitations in the expansion of hSSCs from tissue biopsies for which spermatogenesis is absent or defective. Our aim was to evaluate the first trimester human umbilical cord perivascular cells (FTM HUCPVCs), a novel source of mesenchymal stromal-like cells (MSCs), as potential human feeder cells for standardized hSSC expansion ex vivo. Targeted RNA sequencing analysis demonstrated that CD90+ve FTM HUCPVCs expanded in vitro under germ cell culture conditions express a profile of targeted testicular-associated transcripts that is similar to cultured human CD90+ve testicular adherent cells (hTACs) and secrete LIF, FGF2 and BMP4, key growth factors known to regulate spermatogenesis. We also demonstrated that mitotically inactivated FTM HUCPVCs support the expansion of mouse germ cells and putative SSCs ex vivo and that FTM HUCPVC transplantation promotes in vivo germ cell regeneration after mono-2-ethylhexyl phthalate (MEHP)-induced seminiferous tubule damage in a murine model, including a partial reconstitution of tubular cellular architecture and reestablishment of DAZL and acrosin+ve germ cell layers. Together, these data suggest that FTM HUCPVCs have phenotypical and functional properties that may support repair of the human testicular niche.